Indian Elections, 2014: Commercial Media Pushes Social Media into Focus. (June 2014) - Ranganathan, Maya
The discourse in public space on media at the time of the 2014 Parliamentary elections to 543 seats in 28 states and 7 union territories with 814.5 million voters was characterized by two seemingly disparate but interconnected issues: first, that mainstream media was partisan and wavering in its loyalties to political parties; and secondly, an intense focus on the social media as the most effective means to reach the 23 million first-time voters in a nation with 16 per cent Internet penetration. This article explores the role of the mainstream media in the elections in the context of the shift in India's economic policy which has led to the prioritization of commercial interests by media while relegating other considerations to the background. As a result of the overriding commercial agenda of mainstream media, it has pushed political actors, activists and voters alike onto the new media space. The employment of new media space during the 2014 Indian elections is, thus, to be read in the context of mainstream media's role rather than in the context of new technologies' potential to impact upon democratic politics. It must be noted that media's disregard of other considerations, including ideology, however, cannot be construed as an argument that media were neutral.